2017
DOI: 10.1242/bio.030338
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of thyroid hormone receptor beta in Xenopus tropicalis founders using CRISPR-Cas

Abstract: Amphibians provide an ideal model to study the actions of thyroid hormone (TH) in animal development because TH signaling via two TH receptors, TRα and TRβ, is indispensable for amphibian metamorphosis. However, specific roles for the TRβ isoform in metamorphosis are poorly understood. To address this issue, we generated trβ-disrupted Xenopus tropicalis tadpoles using the CRISPR-Cas system. We first established a highly efficient and rapid workflow for gene disruption in the founder generation (F0) by injectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 49 publications
(70 reference statements)
0
41
0
Order By: Relevance
“…Importantly, the focus of Gephebase is always on genetic variations that emerge naturally -it never includes laboratory variants that were generated by random or directed mutagenesis. Thus the Oca2 CRISPR knockout phenotypes that have been generated in frogs (16) do not have a dedicated Gephebase entry ; the cavefish Oca2 CRISPR/TALEN knockout phenotypes (17,18) do not have a dedicated entry either, but are used as Additional References to support the functionality of the two natural Oca2 null alleles in Gephebase. This makes Gephebase complementary to the Monarch Initiative database, which compiles gene-to-phenotype relationships in humans, as well as in laboratory organisms and mutants generated by reverse genetics, but does not include non-model species such as cavefishes and corn snakes (8,9) .…”
Section: Snapshot Summarymentioning
confidence: 99%
“…Importantly, the focus of Gephebase is always on genetic variations that emerge naturally -it never includes laboratory variants that were generated by random or directed mutagenesis. Thus the Oca2 CRISPR knockout phenotypes that have been generated in frogs (16) do not have a dedicated Gephebase entry ; the cavefish Oca2 CRISPR/TALEN knockout phenotypes (17,18) do not have a dedicated entry either, but are used as Additional References to support the functionality of the two natural Oca2 null alleles in Gephebase. This makes Gephebase complementary to the Monarch Initiative database, which compiles gene-to-phenotype relationships in humans, as well as in laboratory organisms and mutants generated by reverse genetics, but does not include non-model species such as cavefishes and corn snakes (8,9) .…”
Section: Snapshot Summarymentioning
confidence: 99%
“…Therefore, the timing of CRISPR‐Cas9 mediated genome editing is comparable to those of ZFN and TALEN. Ribonucleoprotein (RNP) consisting of the SpCas9 protein in complex with sgRNA has been used in cultured cells and animals (Kim, Kim, Cho, Kim, & Kim, ; Kotani, Taimatsu, Ohga, Ota, & Kawahara, ; Lee et al., ; Sakane et al., ; Shigeta et al., ; Sung et al., ); it shortens the timing of genome editing and overcomes the mosaic property (Kim et al., ; Kotani et al., ). We attempted to accelerate mutagenesis in H. pulcherrimus by using SpCas9 RNP.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot rule‐out that Lin28 also regulates the expression or the function of TH receptors during premetamorphosis and prometamorphosis. Loss‐of‐function studies have shown that TH receptors alpha (THRα) and beta (THRβ) are crucial for the proper timing of metamorphosis and the coordination of changes in different organs . Therefore, Lin28 may regulate the function of THRs in specific tissues in a complex network coordinating the timing of metamorphosis with the proliferation and differentiation of progenitor cells in different tissues.…”
Section: Discussionmentioning
confidence: 99%